2016
DOI: 10.3390/molecules21081007
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and Volatile Composition of a Dry Spearmint (Mentha spicata L.) Extract

Abstract: Abstract:The present paper reports a complete mass spectrometric characterization of both the phenolic and volatile fractions of a dried spearmint extract. Phenolic compounds were analysed by ultra-high performance liquid chromatography-electrospray ionization-mass spectrometry (UHPLC-ESI-MS n ) and a total of 66 compounds were tentatively identified, being the widest phenolic characterisation of spearmint to date. The analysis suggests that the extract is composed of rosmarinic acid and its derivatives (230.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 47 publications
7
67
2
3
Order By: Relevance
“…In any case, the detected ratios were significantly lower than 2.5, which is the suggested threshold for food products to be considered as decalcifiers and poor sources of Ca (Guil, Torija, Giménez, Rodríguez-García, & Himénez, 1996). According to Cirlini et al (2016), organic acids such as citric and malic acid were detected in dried spearmint extracts, without however carrying out quantification of the detected compounds. Considering the role of organic acids as antioxidants (Pereira, Barros, Carvalho, & Ferreira, 2013), this difference could be due to different growing conditions and post-harvest processing.…”
Section: Organic Acids Contentmentioning
confidence: 93%
“…In any case, the detected ratios were significantly lower than 2.5, which is the suggested threshold for food products to be considered as decalcifiers and poor sources of Ca (Guil, Torija, Giménez, Rodríguez-García, & Himénez, 1996). According to Cirlini et al (2016), organic acids such as citric and malic acid were detected in dried spearmint extracts, without however carrying out quantification of the detected compounds. Considering the role of organic acids as antioxidants (Pereira, Barros, Carvalho, & Ferreira, 2013), this difference could be due to different growing conditions and post-harvest processing.…”
Section: Organic Acids Contentmentioning
confidence: 93%
“…Our previous studies have reported significant amounts of salvianolic acid B in transformed root cultures and the roots of a 1-year-old intact plant of D. forrestii (Weremczuk-Jeżyna et al 2016). In contrast to caffeic and rosmarinic acid, salvianolic acids are not common and have been found in only a few species (Ożarowski et al 2016;Ribeiro et al 2016;Cirlini et al 2016). They are mainly obtained from members of the Salvia genus, especially Salvia milthiorrhiza (Li et al 2009a).…”
Section: Identification Of Phenolic Compounds Of the Hydromethanolic mentioning
confidence: 99%
“…However, a significant number of VOCs attributable to the metabolism of yeast strains increased in concentration during the AF. Specifically, aldehydes and alcohols have very pleasant aromas, the first of fat, citrus, green, almond, burnt, sugar and sweet aromas, whereas the second one of alcoholic, flower, nut, hyacinth aromas (Bianchi et al, 2007;Cirlini et al, 2016;Dall'Asta et al, 2011;Fariña et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Short chain acids such as acetic acid, have spicy and sour flavors and aromas, while butanoic acid and hexanoic acids are linked to a rancid and sweat aroma (Barra et al, 2010;Kaack et al, 2005). In final products, the furfuraldehyde and benzaldehyde were also detected at high levels, they are usually associated with sweet, pungent aromas and almond aromas (Kaack et al, 2005;Cirlini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%